2016
DOI: 10.1155/2016/4323792
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Home-Based Family-Centred Early Habilitation Program on Neurobehavioural Outcomes of Very Preterm Born Infants: A Retrospective Cohort Study

Abstract: Preterm children have an increased risk of neurodevelopmental impairments which include psychomotor and language retardation. The objectives of the present retrospective cohort study were to examine the effects of an individually adapted, home-based, and family-centred early developmental habilitation program on neurodevelopmental and behavioural outcomes of very preterm children compared with a standard follow-up at 2 years' corrected age. Enrolled infants were retrospectively assigned to the intervention gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 45 publications
0
12
0
6
Order By: Relevance
“…As a result, the early stage of infants is significant in brain development. The relationship between experiences and CNS plasticity two-way, which means the brain can produce adaptive behavioral changes after external stimulus [11]. By providing positive interventions, the potential of the brain can be activated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the early stage of infants is significant in brain development. The relationship between experiences and CNS plasticity two-way, which means the brain can produce adaptive behavioral changes after external stimulus [11]. By providing positive interventions, the potential of the brain can be activated.…”
Section: Discussionmentioning
confidence: 99%
“…Family-centered care is a philosophy of care that emphasizes the integrity of the family and individualizing care [18]. A retrospective cohort study focused on the environmental enrichment, parent-guided environmental interaction, and infant development assessed the effect of a home-based family-centered early developmental habilitation program, finding that both cognitive and behavioral outcomes were improved [11].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the data on GA and birth weight present in Table 1, this study found that the lower the gestational age and the birth weight, the more frequent and the greater the follow-up visits are. Some researches show this need for more frequent follow-up when they affirm that low birth weight and prematurity are related to an increase in morbidity and mortality, chronic conditions and readmissions 2 - 3 , 9 , 19 , 27 - 31 , as well as to the greater risk of growth deficit 3 , 21 , developmental delays and cognitive and behavioral problems 3 , 7 , 31 - 32 . In addition, growth must be closely monitored in the first year of life of patients with this profile, thus ensuring optimal brain nutrition and reducing risks of neurodevelopmental delays 19 , 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Most of these diagnoses are found in premature infants born with less than 1,500g, neuropathic and those with longer length of stay 2 - 3 , 19 , and in some studies, they are also present in chronic infants coming from the NICU 27 and in those who most needed readmissions 9 , 11 , 29 . Neonatal conditions, such as prematurity, asphyxia, infections and hyperbilirubinemia, were associated with sequelae and compromised survival in a retrospective Italian cohort performed with 123 subjects 7 . Anemia must be monitored and treated frequently because it can lead to low weight gain and changes in development 19 , 33 .…”
Section: Discussionmentioning
confidence: 99%
“…A intervenção precoce consiste no conjunto de ações que oferecem à criança experiências sensóriomotoras necessárias desde o nascimento, para potencializar um desenvolvimento neuropsicomotor adequado, através de uma avaliação criteriosa e assistência fisioterapêutica personalizada (FORMIGA et al, 2010). É necessário aproveitar a janela de tempo mais favorável para a plasticidade cerebral, e estabelecer uma intervenção protetora e/ou restauradora o mais precocemente possível (POGGIOLI et al, 2016;CAMARGO et al, 2017). O objetivo desse estudo é realizar uma revisão bibliográfica para identificar as principais estratégias fisioterapêuticas de intervenção precoce nos recém-nascidos prematuros em unidade de terapia intensiva neonatal.…”
Section: Introductionunclassified